Future scenarios : “we are all failed states, now” (2020)
As I write this, the constitutional environment of the United States is experiencing its greatest stresses since the American Civil War. A viral pandemic has engulfed the world and especially stricken the United States; as of this writing more than 3 million coronavirus cases have been reported in the United States, more than in any other country. Although the United States has about 4.2% of the global population, it has suffered 25% of the deaths worldwide— more than 132,000 Americans have died from the COVID-19 virus. Partly as a consequence of this viral apocalypse, US unemployment is experiencing levels approaching 20%1 —numbers not seen since the Great Depression, and US gross domestic product is expected to contract by 7% in a single year.2 The chairman of the Federal Reserve has predicted a steep recession of uncertain length3 and the federal debt has climbed to levels unseen outside of wartime